1998
DOI: 10.1159/000024915
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of the Specificity of Enzyme Immunoassays for the Detection of Rotavirus and Adenovirus in Fecal Specimens

Abstract: A variable rate of false-positive results may be observed with commercial enzyme immunoassays (EIAs) for the detection of rotavirus and adenovirus antigen in stool specimens, depending on the quality of the reagents and the presence of potentially interfering substances in stool samples. The present study was performed in an attempt to improve the specificity of current commercial rotavirus and adenovirus EIAs without significant loss of sensitivity by optimizing the cut-off value. A collective of 174 stool sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 16 publications
(9 reference statements)
1
10
0
Order By: Relevance
“…Some investigators have postulated that EIAs are probably a better standard method for detection of rotaviruses than is EM due to the low sensitivity of the latter (2, 5); however, in these studies EM was performed without ultracentrifugation of samples, which has been demonstrated to be an essential step in achieving maximum sensitivity (7). Rabenau et al (14) have also evaluated the Ridascreen rotavirus test along with a panel of other assays and shown that this test, after adjustment of the cutoff value, exhibited superior sensitivity and specificity values for the detection of rotaviruses, which is in accordance with our study. In contrast, the false-positive results of the Pathfinder rotavirus assay could not be erased by increasing the cutoff value ( Table 2; Fig.…”
Section: %]) Because the Pathfinder Test Issupporting
confidence: 91%
“…Some investigators have postulated that EIAs are probably a better standard method for detection of rotaviruses than is EM due to the low sensitivity of the latter (2, 5); however, in these studies EM was performed without ultracentrifugation of samples, which has been demonstrated to be an essential step in achieving maximum sensitivity (7). Rabenau et al (14) have also evaluated the Ridascreen rotavirus test along with a panel of other assays and shown that this test, after adjustment of the cutoff value, exhibited superior sensitivity and specificity values for the detection of rotaviruses, which is in accordance with our study. In contrast, the false-positive results of the Pathfinder rotavirus assay could not be erased by increasing the cutoff value ( Table 2; Fig.…”
Section: %]) Because the Pathfinder Test Issupporting
confidence: 91%
“…3 and 4 -siblings with respiratory symptoms). of cut-off can improve EIA characteristic [10]. According to the information provided by the manufacturer, the detection limit of Ridascreen and IDEIA is between 10 5 and 10 6 viral particles per ml based on electron microscopy.…”
Section: Discussionmentioning
confidence: 99%
“…Since the handling of classical shell vials is laborious, a more convenient RCA was evaluated in the laboratory to improve the diagnosis of respiratory adenovirus infection. This method was described for detection of enteric adenoviruses [10,16]. The disadvantage of shell vial assay is the tedious manual preparation and washing of cover slips.…”
Section: Nomentioning
confidence: 99%
“…Assays for the detection of rotavirus and adenovirus antigens were carried out as previously described [16] using Ridascreen Adenovirus and Ridascreen Rotavirus ELISA tests (r-biopharm).…”
Section: Antigen Testmentioning
confidence: 99%